2022
DOI: 10.11149/jkaoh.2022.46.2.56
|View full text |Cite
|
Sign up to set email alerts
|

A study on trends of dental caries disparities according to household income level of children and adolescents using data from the Korea National Health and Nutrition Examination Survey

Abstract: Objectives:The purpose of this study is to investigate the trend of dental caries inequalities according to the household income level of children and adolescents, using data from Wave 4 (2007Wave 4 ( -2009 to Wave 7 (2016Wave 7 ( -2018 of the Korea National Health and Nutrition Examination Survey (KNHANES). Methods: The raw data were obtained from the website of KNHANES. The data by year within each wave were integrated and used for the analysis. In accordance with the guidebook for data users, the experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(7 reference statements)
0
1
0
2
Order By: Relevance
“…However, recent studies have reported contradictory results. The study on dental caries disparities by household income level by Jung [30] analyzed data spanning the 4th through 7th National Health and Nutrition Examination Surveys and found no significant difference in dental caries prevalence across household income levels, and no clear disparities could be discerned. The results of our study reported that there is no difference in the prevalence of dental caries based on income levels by region, as well as that the economic status of the metropolitan level of the region does not affect the prevalence of dental caries in the county level of the region.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have reported contradictory results. The study on dental caries disparities by household income level by Jung [30] analyzed data spanning the 4th through 7th National Health and Nutrition Examination Surveys and found no significant difference in dental caries prevalence across household income levels, and no clear disparities could be discerned. The results of our study reported that there is no difference in the prevalence of dental caries based on income levels by region, as well as that the economic status of the metropolitan level of the region does not affect the prevalence of dental caries in the county level of the region.…”
Section: Discussionmentioning
confidence: 99%
“…이 지침 10) 에 따르면 치아우식의 치료 필요 정도를 평가한 임상적 요인과 더불어 예방적 치과 이용, 칫솔질, 불소치약 사 용, 단맛 간식•음료 섭취 등 생활습관 요인의 개별항목을 기준에 따라 안전, 주의, 위험으로 판정하고 이를 종합하여 개인의 우식 위험도를 낮음, 보통, 높음으로 판정한다. 그런데 아동의 치아우식 위험요인에 대한 국내 근거 자료는 고위험군 [11][12][13] 대상이거나 칫솔질 14) , 가구소득 수준 15) 료만을 누리집을 통해 제공한다 16) . 저자는 2023년 3월에 국민건강영 양조사 누리집 17) 3).…”
Section: 서 론unclassified
“…까지의 국민건강영양조사 자료를 분석하여 한국인의 구강건강 불평등 의 전체적인 추이를 파악하기 위한 일련의 연구를 계획하였고, 아동• 청소년의 소득수준에 따른 치아우식 불평등 추이 보고 21) 에 이어 성인 의 소득수준에 따른 치아우식, 깊은 치주낭, 다수 치아 상실의 불평등 추이를 두 번째 결과물로써 보고하고자 한다.…”
Section: 이에 저자는 2007년(제4기 1차연도)부터 2020년(제8기 2차연도)unclassified